Clinical metabolomics reveals potential diagnostic biomarkers in serum samples from patients with generalized ligamentous laxity - Zhang, Yu; Hu, Xiaochao; Chen, Feng; Liu, Tongtong; Cai, Ping; Liu, Shijia; Sun, Luning (Frontiers in Molecular Biosciences, 2025)
ObjectivesDiscovering the potential metabolic alterations underlying generalized ligamentous laxity (GLL) is crucial for identifying new therapeutic targets and improving patient prognosis. Serum metabolites could mirror systemic and local alterations and help understand the metabolic features of GLL. The present work aimed to determine serum biomarkers for GLL diagnosis and to unveil metabolic pathways linked to GLL.DesignProspective, observational cohort study.MethodsIn this study, serum sample collection was conducted from 65 GLL and 35 healthy control (HC) cases. The obtained specimens were assessed by ultra-performance liquid chromatography high-resolution mass spectrometry (UPLC-HRMS). Orthogonal partial least squares-discriminant analysis (OPLS-DA), random forest (RF), binary logistic regression (BLR) and receiver operating characteristic (ROC) analyses were applied to screen and validate biomarkers.ResultsTotally 24 small-molecules were considered differentially expressed metabolites. Of these, hexadecanamide was found to be a specific biomarker for differential diagnosis of GLL, with an area under the ROC curve (AUC) of 0.907. Additionally, the α-linolenic acid and linoleic acid metabolism had the most substantial alteration among various pathways in GLL cases. The altered pathway of α-linolenic acid and linoleic acid metabolism affected bone mineral density and bone metabolism in GLL patients, leading to enhanced inflammation or fracture of the bone and joints. Joint inflammation and dislocation led to systemic ligament relaxation, which induced and aggravated musculoskeletal injury.ConclusionThrough identification of serum biomarkers and analysis of metabolic pathways, the current study provided novel insights into GLL pathogenesis.